Internet of Things based Durability Monitoring and Assessment of Reinforced Concrete Structures - Woubishet Zewdu Taffese; Ethiopia Nigussie; Jouni Isoaho (Netherlands, 2022)
We present a conceptual framework for continuous in-service durability monitoring and assessment of reinforced concrete (RC) structures. Conventional durability assessments are carried out through laboratory testing of samples taken destructively from the structures, which are labor intensive, time consuming and costly. By employing internet of things, continuous nondestructive in-service monitoring of structures can be realized in a cost-effective manner. The availability of long-term monitored data along with the use of intelligent data analysis enables capturing of the complex nonlinear interaction of durability controlling parameters, making the structures' condition assessment more reliable. The reliability of the assessment results is highly beneficial for stakeholders to plan proactive maintenance, which in turn extends the service life of the structures. (C) 2019 The Authors. Published by Elsevier B.V.
The 16th International Conference on Mobile Systems and Pervasive Computing (MobiSPC 2019)